Relevance of the Warburg Effect in Tuberculosis for Host-Directed Therapy - Cumming, Bridgette M.; Pacl, Hayden T.; Steyn, Adrie J. C. (Frontiers in Cellular and Infection Microbiology, 2020)
Tuberculosis (TB) kills more people every year than any other infectious agent. This epidemic is exacerbated by the ongoing development of multi-drug resistance and HIV co-infection. Recent studies have therefore focused on identifying host-directed therapies (HDTs) that can be used in combination with anti-mycobacterial drugs to shorten the duration of TB treatment and improve TB outcomes. In searching for effective HDTs for TB, studies have looked toward immunometabolism, the study of the role of metabolism in host immunity and, in particular, the Warburg effect. Across a variety of experimental paradigms ranging from in vitro to the clinic, studies on the role of the Warburg effect in TB have produced seemingly conflicting results and contradictory conclusions. To reconcile this literature, we take a historical approach to revisit the definition of the Warburg effect, re-examine the foundational papers on the Warburg effect in the cancer field and explore its application to immunometabolism. With a firm context established, we assess the literature investigating metabolism and immunometabolism in TB for sufficient evidence to support the role of the Warburg effect in TB immunity. The effects of the differences between animal models, species of origin of the macrophages, duration of infection and Mycobacterium tuberculosis strains used for these studies are highlighted. In addition, the shortcomings of using 2-deoxyglucose as an inhibitor of glycolysis are discussed. We conclude by proposing experimental criteria that are essential for future studies on the Warburg effect in TB to assist with the research for HDTs to combat TB.